Ethanolic Extract of Citrus reticulata Peel Inhibits the Migration of WiDr Colon Cancer Cells - Astuti, Yoni; Primasari, Aulia (Indonesian Society for Cancer Chemoprevention, 2020)
Colorectal cancer is third rank on the cancer cases in Indonesia. To cure the cancer needs big cost and lot of effort. On the other side, the side effect of medicine or chemotherapy on patient need to reduce. Cancer cell spread to other tissue based on its migration and invasion ability. Citrus reticulata peel contains flavonoid such as Tangeretin and Nobiletin, both of this compounds have anticancer activity. The aims of this study is to reveals the potency of ethanol extract of Citrus reticulata peel on the inhibition of migration on WiDr colon cancer cells. The toxicity of ethanol extract of Citurs reticulata peel on WiDr colon cancer line was measured using 3-(4,5-dimethyltiazol-2-il)-2,5-diphenyltrazolium bromide (MTT) assay and investigate the cell migration was using scratch wound healing assay. The ethanol extract of Citrus reticulata peel showed the value of inhibitory concentration 50 (IC50) was 184.5 μg/mL, this result categorize as moderate cytotoxic. Meanwhile the migration assay showed that the deceleration of migration occurred on 0.5 IC50, 0.33 IC50 and 0.25 IC50 during 24 h and 36 h incubation, event thought there were not significant different (p>0.05). The ethanol extract of Citrus reticulata peel has a potential migration inhibition on WiDr cell line.Keywords: Citrus reticulata, WiDr cell line, migration